The application value of serum Th1/Th2 cytokines combined with tumor markers in the diagnosis of HR-HPV-positive cervical cancer: Serum Th1/Th2 cytokines and tumor markers in cervical cancer - Cao, Xia; Zhang, Xuemei; Zhang, Jingpo; Zhong, Xiaodang; Hu, Shanshan (Journal of Medical Biochemistry, 2025)
Objective: To analyze the value of serum helper T-cell 1 (Th1)/helper T-cell 2 (Th2) cytokines combined with tumor markers in the diagnosis of high-risk human papillomavirus (HR-HPV)-positive cervical cancer.Methods: Forty-nine patients with HR-HPV-positive cervical cancer admitted to the hospital from January 2020 to June 2024 were selected as the study group, and 49 patients with HR-HPV-positive benign cervical diseases of the same age group admitted to the hospital during the same period were selected as the control group.The basic data, serum Th1/Th2 cytokines [interleukin (IL)-10, IL-6, interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α)], and tumor markers [squamous cell carcinoma antigen (SCCAg), carbohydrate antigen 199 (CA199) levels and cytokeratin 19 fragment antigen 21-1 (CYFRA21-1)] of the two groups were compared, and the serum Th1/Th2 cytokine levels of patients with different clinicopathological characteristics in the study group were compared. Pearson correlation analysis was used to analyze the correlation between the levels of serum Th1/Th2 cytokines and tumor markers in patients with HR-HPV-positive cervical cancer. A receiver operating characteristic (ROC) curve was drawn to analyze the value of serum Th1/Th2 cytokines and tumor markers in the diagnosis of HR-HPV-positive cervical cancer.Results: The levels of serum IL-10, IL-6, IFN-Y, TNF-a, SCC-Ag, CA199 and CYFRA21-1 in the study group were greater than those in the control group (P
Keywords: Serum Th1/Th2 cytokines; Tumor markers; Diagnosis; HR-HPV-positive; Cervical cancer